Exploring the influence of natural features on soil mesofaunal communities in agricultural landscapes through DNA metabarcoding - Angeli Sahdra; Angeli Sahdra; Monica R. Young; Lori A. Phillips; Niloofar Alavi; David R. Lapen; Jeremy T. Kerr; Marla D. Schwarzfeld (Frontiers in Sustainable Food Systems)
Soil mesofauna critically support organic matter decomposition and nutrient cycling, as well as regulating pests and diseases. Agricultural activities can physically and chemically influence soil mesofauna communities, thereby impacting the ecosystem services they provide. Conserving natural features in agricultural environments is well known to support biodiversity and associated ecosystem services, yet soil mesofauna communities and their functions in such features require further study. We sampled the soil mesofaunal communities (focusing on Acari [mites] and Collembola [springtails]) in agriculturally-dominated landscapes in southeastern Ontario, Canada. Semi-natural features were represented by drainage ditch banks with varying amounts of woody vegetation to different kinds of forested blocks. Specimens were extracted using Berlese funnels, and COI metabarcoding was conducted on the bulk specimen samples. A total of 585 operational taxonomic units (OTUs; a proxy for species) were identifiable based on DNA sequences, 390 of which belonged to either Acari (273) or Collembola (117); however, it was rarely possible to identify specimens to species-level. Mesofaunal richness did not differ among habitat types but community composition varied between low woody-vegetation drainage bank sites and forested blocks. Maintaining heterogeneous natural and semi-natural features appears to increase the overall diversity of mesofauna on the landscape, and even small forest patches support forest-associated soil biodiversity in this agricultural region.